Retinal counterion switch in the photoactivation of the G protein-coupled receptor rhodopsin - Yan, Elsa C. Y. (National Academy of Sciences, 2003)
The biological function of Glu-181 in the photoactivation process of rhodopsin is explored through spectroscopic studies of site-specific mutants. Preresonance Raman vibrational spectra of the unphotolyzed E181Q mutant are nearly identical to spectra of the native pigment, supporting the view that Glu-181 is uncharged (protonated) in the dark state. The pH dependence of the absorption of the metarhodopsin I (Meta I)-like photoproduct of E181Q is investigated, revealing a dramatic shift of its Schiff base pK(a) compared with the native pigment. This result is most consistent with the assignment of Glu-181 as the primary counterion of the retinylidene protonated Schiff base in the Meta I state, implying that there is a counterion switch from Glu-113 in the dark state to Glu-181 in Meta I. We propose a model where the counterion switch occurs by transferring a proton from Glu-181 to Glu-113 through an H-bond network formed primarily with residues on extracellular loop II (EII). The resulting reorganization of EII is then coupled to movements of helix III through a conserved disulfide bond (Cys110–Cys187); this process may be a general element of G protein-coupled receptor activation.